Innovation Systems : World Bank Support of Science and Technology Development - Goel, Vinod K. (Washington, DC: World Bank, 2013)
Innovation systems and science and technology (S&T) projects supported by the World Bank have taken on many forms in the past several years. The Bank's involvement in industrial technology projects started in the 1970s, with Israel and Spain numbering among the first countries to receive support in the form of industrial technology development. This paper reviews the lessons learned in S&T projects that have been supported by the Bank, with an emphasis on the examples of the past decade (1989-2003). Projects and their components were included in this review if their objectives included the use of scientific and technological knowledge to improve development. The review included 51 projects, in an aggregate amount of over US$4.2 billion; not including agricultural research projects. The amounts invested in individual projects ranged from US$3 million to US$300 million, with a mean project size of about US$58 million. The paper discusses the concept of the knowledge-based economy (KE) and its relation with the S&T sector, and then identifies the main themes of KE projects, groups them by the four pillars of the knowledge economy, and summarizes the key lessons learned. Since the Bank experience is most substantial in the areas of innovation systems and related policy frameworks, the review focuses on industrial technology development and on building national innovation systems. It touches briefly on the themes of education, and information and communications technology, with the aim of providing the proper context for the main study. A List of Projects is included in Box 1, and brief descriptions of these projects are in Annex B.